Cecília Meireles: vida e obra (Revista do Centro de Estudos Portugueses, 2001)
Texto-verbete de Cecília Meireles, (constante cio Dicionário Critico de Escritoras Brasileiras ia ser publicado em meados de 2002), abrangendo dados biobibliográficos, acrescidos de juízo crítico acerca da arte poética ceciliana, em relação ao contexto do Modernismo brasileiro e da poesia em geral, na primeira metade do século XX. The text is the Cecília Meireles entry to appear in TbcCriticai Dictionary of Brazilian Women Autbors that will be published in the course of 2002. It comprises biobibliographical data, followed by criticai comments on that authoi’s poetics, relatory it to the Brazilian modernist context and to Brazilian poetry in general, in the lst half of the 20th century.